The Dark Triad traits and intelligence: Machiavellians are bright, and narcissists and psychopaths are ordinary. (1st December 2018) - Kowalski, Christopher Marcin; Kwiatkowska, Katarzyna; Kwiatkowska, Maria Magdalena; Ponikiewska, Klaudia; Rogoza, Radosław; Schermer, Julie Aitken
Abstract: Extant empirical research, despite some theoretical descriptions, has consistently demonstrated that the Dark Triad is not related to general mental ability. In the present study, we investigated the relationship between the Dark Triad of personality (narcissism, Machiavellianism, and psychopathy) and fluid intelligence. A sample of 128 Polish high school students ( M age = 16.89 years; SD age = 0.31; 28.1% of the sample were boys) completed the Polish translation of the Short Dark Triad and the Raven's Standard Progressive Matrices. Hypotheses were tested using a structural equation model, which fit the data well. As predicted, we found that of the three Dark Triad traits, only Machiavellianism was significantly predicted by fluid intelligence. Our findings are discussed in light of previous research and theory. Highlights: Investigated the relationship between the Dark Triad and Fluid intelligence Fluid intelligence significantly predicted Machiavellianism. Fluid intelligence was not a significant predictor of narcissism or psychopathy.